2022
DOI: 10.24292/01.mf.0122.9
|View full text |Cite
|
Sign up to set email alerts
|

10 reasons why to use citicoline

Abstract: Citicoline is an endogenous compound and play important role in cellular metabolism. It may be helpful in treatment of stroke, Parkinson and Alzheimer disease, glaucoma, after head injury etc. The safety of citicoline was confirmed in many studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Kopka and Sochacki [ 871 ] concluded that in the light of currently available scientific reports, citicoline can be consider as a safe and useful substance for many indications and it is also characterized by a lack serious side effects as well as very good tolerance among patients. Thus, there are 10 reasons why to use citicoline:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kopka and Sochacki [ 871 ] concluded that in the light of currently available scientific reports, citicoline can be consider as a safe and useful substance for many indications and it is also characterized by a lack serious side effects as well as very good tolerance among patients. Thus, there are 10 reasons why to use citicoline:…”
Section: Discussionmentioning
confidence: 99%
“…Kopka y Sochacki [ 871 ] concluyeron que, a la luz de los informes científicos disponibles en la actualidad, la citicolina puede considerarse una sustancia segura y útil para muchas indicaciones, y también se caracteriza por la ausencia de efectos secundarios graves, así como por una muy buena tolerancia entre los pacientes. Por lo tanto, hay 10 razones por las que usar citicolina:…”
Section: Conclusionesunclassified